Steel design - Segui, William T. (Thomson, 2007)
Steel design, fourth edition covers the fundamentals of structural steel design. The emphasis is on the design of memebers and their connections rather than the integrated design of buildings. This book intended for junior-and senior-levelengineerings students, although some of the later chapters can be used in graduate courses. Practicing civil engineers who need a review of current practice and the current AISC specification and maual will find the book useful as a reference. Students should have a background in mechanics of materials and analysis of statically determinate structures.